Persebaran Bangunan dam Di Bali Pada Abad Ke-20 - Si Gede Bandem Kamandalu; I Wayan Wardi; Coleta Palupi Titasari (Badan Riset dan Inovasi Nasional (BRIN), 2023)
The Ethical Politics implemented by the Dutch at the beginning of the 20th century was an effort made to